Comparative study between poorly differentiated thyroid cancer and anaplastic thyroid cancer: real-world pathological distribution, death attribution, and prognostic factor estimation - Zhang, Kun; Wang, Xinyi; Wei, Tao; Li, Zhihui; Zhu, Jingqiang; Chen, Ya-Wen (Frontiers in Endocrinology, 2024)
Background: The clinic-pathological boundary between poorly differentiated thyroid cancer (PDTC) and anaplastic thyroid cancer (ATC) is unclear due to a wide spectrum of histopathological features and rarity of the disease. In addition to that, with the highest mortality rate and non-standard treatment modality, the PDTC/ATC population has not been subjected to comprehensive description and comparison to the extent of histological characteristics, therapeutic response, prognostic factors, and death attribution analysis. Method: A total of 4947 PDTC/ATC patients from 2000 to 2018 were identified from the Surveillance, Epidemiology, and End Results (SEER) database. Kaplan-Meier survival curve estimation and Cox proportional hazard regression were applied. Results: Overall, the 5- and 10-year DSS for PDTC was 71.9% and 68.0%, respectively, while the 5- and 10-year OS is 59.3% and 51.2%. The median survival time for ATC patients was 3 months with 1-year OS being 26.9% and 1-year DSS being 31.2%. During the follow-up period, 68.1% of the PDTC/ATC cohort were dead, 51.6% of which were attributed to thyroid malignancies and 16.5% to non-thyroid causes. The top 3 common non-thyroid cause-of-death were miscellaneous cancers, lower respiratory system disease, and heart disease. Histological feature of papillary thyroid cancer (PTC) was the leading pathological category for PDTC patients (51.7%), while 76.7% of ATC patients’ pathological features was characterized as unidentifiable. Sarcoma histological characteristics found in ATC cases suffer the highest overall mortality (vs PTC, HR=2.61, 95% CI 1.68-4.06, P<0.001). Older age unidentifiable histology feature, more advanced AJCC N1b, AJCC M1, and SEER stage, tumor size larger than 5cm, and more invasive tumor extension were independent bad outcome predictors. Conclusion: The populational analysis of PDTC/ATC cohort have provided reliable support for better understandings of the difference between PDTC and ATC cases and the guidance of clinical practice and further studies.